Analisis Willingness to Pay Masyarakat Kelurahan Antapani Tengah Menuju Optimalisasi TPS3R - Muhammad Faathir Alhakam; Iwan Juwana (Fakultas Teknik, 2019)
Central Antapani sub-district is one of the regions in Bandung City that has a reduce reuse recycle waste processing facility, namely TPS 3R Cibatu. There are still problems that cause solid waste management did not run optimally. The manager of TPS 3R Cibatu confirmed that there would be an optimization attempt. But, the limited funds from previous solid waste retribution became a problem to accelerate that solid waste management optimization. The research’s purpose is to analyze Willingness to Pay (WTP) from the community of Central Antapani sub-district in the optimization attempt of TPS 3R Cibatu, because there has not been researched that done the study of the amount of the community’s WTP. The method used is the Contingent Valuation Method (CVM) and bidding game technique. The number of respondents that being interviewed is 160 householders, with the details of 135 householders who are willing to pay and 25 householders who are not. Based on the interview result, obtained the average WTP of Rp. 7.163/month and the total WTP of Rp. 16.079.000/month. Based on the statistical analysis, known that the factors that affected the WTP value’s respondents are educational level and solid waste retribution fund.